IMPLEMENTATION OF MANDAILING NATAL REGENT REGULATION NUMBER 36 OF 2022 REGARDING THE GAS LEAK INCIDENT OF SORIK MARAPI PLTP FROM AN INDUSTRIAL AND SCIENTIFIC PERSPECTIVE - Khoirotun Nisa Pulungan; Zulkifli Nas (Journal Analytica Islamica, 2026)
This study examines the implementation of Mandailing Natal Regent Regulation Number 36 of 2022 concerning the management of gas leak incidents ats at the Sorik Marapi Geothermal Power Plant (PLTP). The regulation was enacted as a preventive and responsive policy to protect communities living in high-risk areas surrounding geothermal industrial activities. Using an empirical legal research design with a qualitative case study approach, data were collected through in-depth interviews with local government officials, environmental agencies, disaster management authorities, civil society organizations, and affected residents, as well as field observations and document analysis. The findings indicate that although the regulation provides a comprehensive normative framework for emergency preparedness covering early warning systems, evacuation procedures, medical response, and inter-agency coordination its implementation has not been fully effective. Key shortcomings include the absence of functional gas detection and warning systems in residential areas, unstructured evacuation mechanisms, reactive rather than preventive medical responses, and weak coordination between local authorities and geothermal operators.